Adverse events associated with discontinuation of the biologics/classic systemic treatments for moderate‐to‐severe plaque psoriasis: data from the Spanish Biologics Registry, Biobadaderm. (6th June 2017) - Belinchón, I.; Ramos, J.M.; Carretero, G.; Ferrándiz, C.; Rivera, R.; Daudén, E.; De la Cueva‐Dobao, P.; Gómez‐García, F.J.; Herrera‐Ceballos, E.; Sánchez‐Carazo, J.L.; López‐Estebaranz, J.L.; Alsina, M.; et al.
Abstract: Background: Little is known about the adverse events (AEs) that lead to suspension of systemic treatments for psoriasis in clinical practice. Objective: The study aimed to investigate AEs associated with discontinuation of systemic therapy in patients with psoriasis in a clinical setting (Biobadaderm). Materials and methods: Multicentre, prospective, cohort study of patients with moderate‐to‐severe plaque psoriasis receiving systemic therapies from January 2008 to November 2015, in 12 hospitals in Spain. The incidence rate (IR) was used to compare biologics and classic systemic therapies. Results: A total of 4218 courses of treatment were given to 1938 patients. A total of 447 (11%) treatments were discontinued due to AEs. The IR of AE associated with discontinuation of systemic therapies was 13 events/100 patient‐years (PY) (95% CI: 12.14–13.93), 9.34 events/100 PY (95% CI: 8.44–10.33) for biologics and 19.67 (95% CI: 17.9–21.6) events/100 PY for classics ( P < 0.001). Of 810 discontinuation‐related AEs, 117 (14%) were serious. The highest IRs were for cyclosporine [49.18/100 PY (95% CI: 41.91–57.72)] and infliximab [26.52/100 PY (95% CI: 20.98–33.51). Ustekinumab presented the lowest IR (2.6/100 PY (95% CI: 1.83–3.69). Limitations: Observational study with potential selection bias. Conclusion: Biologic therapies are associated with a lower rate of discontinuation‐related AEs than are classic therapies in real clinical practice. Ustekinumab showed the lowest incidence.